Seasonal carbon-balance of a semi-desert temperate grassland ecosystem over a year period - Balogh, János (Acta Biologica Szegediensis, 2002)
Temperate grassland ecosystems are important components of the global carbon cycle. Our object of investigation, the semi-arid sand grassland community (Festucetum vaginatae danubiale) occurs widely in Hungary. A closed-loop portable IRGA system connected to a chamber appropriate for stand-scale measurements was used to measure C02-exchange over a semi-desert temperate grassland from November 2000 to November 2001. Daily and yearly carbon balances were calculated by integration of net CO, assimilation rates. The investigated sandy grassland proved to be a relatively strong source of carbon (-131.48g C.m 2.year1) as calculated over the year, probably caused also by nutrient limitations (characteristic of thes e grasslands) during the short periods when water supply was not limiting photo-synthesis.